Behavioral factor analysis of the accuracy in using gastritis drugs at the Puskesmas Arjuno in Malang City with the Health Belief Model (HBM) approach - Firdha Julianty Sukma; Ika Ratna Hidayati; Liza Pristianty (Universitas Muhammadiyah Malang, 2021)
This study aims to analyze the behavioral factors according to the Health Belief Model (HBM) theory, which affects the accuracy in using gastritis drugs at Arjuno Health Center, Malang City. This research is a non-experimental study with an analytical observational research design. The instrument used a valid and reliable questionnaire. There were two variables used, the independent variables, namely the factors of the theory of the HBM (Perceived susceptibility, Perceived severity, Perceived Benefits, Perceived barriers, and Self Efficacy), and the dependent variable is the proper usage of gastric drugs. The number of samples used int this study was 80 respondents. The regression test results on each factor of HBM theory on the accuracy of using gastritis drugs (p < 0.05) means significantly affected the accuracy of using gastritis drugs except for perceived barriers, which is a significant value of 0.301 > 0.05. This result is relevant to the theory which states that the higher perceived barriers, the correct use of drug will be lower. Then for the Anova test, all independent variables were tested with the dependent variable and the results means that there is an influence between the HBM theory and the accuracy of using gastritis drugs. If measured simultaneously, factors from the HBM affect the accuracy in using gastritis drugs with a significant effect of 64.9%.